2004
DOI: 10.1023/b:netn.0000023380.38300.25
|View full text |Cite
|
Sign up to set email alerts
|

Internet Interconnection Economic Model and its Analysis: Peering and Settlement

Abstract: Peering has been a core concept to sustain Internet industry. However, for the past several years, many ISPs broke their peering arrangement because of asymmetric traffic pattern and asymmetric benefit and cost from the peering.Even though traffic flows are not a good indicator of the relative benefit of an Internet interconnection between the ISPs, it is needless to say that cost is a function of traffic and the only thing that we can know for certain is inbound/outbound traffic volumes between the ISPs. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 1 publication
2
28
0
Order By: Relevance
“…For example, [20] presents a simple traffic model between local ISPs and uses a simple economic model to predict when these ISP would use no-payment peering rather than customer-provider peering for their local traffic. In [17], the authors give an interesting analysis of how transit and customer prices are set in a network consisting of multiple ISPs.…”
Section: Related Workmentioning
confidence: 99%
“…For example, [20] presents a simple traffic model between local ISPs and uses a simple economic model to predict when these ISP would use no-payment peering rather than customer-provider peering for their local traffic. In [17], the authors give an interesting analysis of how transit and customer prices are set in a network consisting of multiple ISPs.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, the peering agreement could be considered as a preliminary agreement of collaboration between two Internet providers. Second, some recent studies have shown that asymmetric effect was one major factor that has a negative and significant impact on tying a peering agreement (Carter and Wright, 2003;Weiss and Shin, 2004;Badasyan and Chakrabarti, 2008;Shrimali and Kumar, 2008;Jahn and Prüfer, 2008;Lippert and Spagnalo, 2008). Internet providers prefer tie peering with providers of similar size, otherwise transit agreements.…”
Section: Introductionmentioning
confidence: 99%
“…Further, we extended studies by examining the benefits of the customer providers only, which purchased transit services [12]. However, the remaining literature on the economics of interconnection considers the intercarrier compensation based only on the flows of traffic [2,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%